Dynamic partitioning of branched-chain amino acids-derived nitrogen supports renal cancer progression - Sciacovelli, Marco; Dugourd, Aurélien; Jimenez, Lorea Valcarcel; Yang, Ming; Nikitopoulou, Efterpi; Costa, Ana S. H.; Tronci, Laura; Caraffini, Veronica; Rodrigues, Paulo; Schmidt, Christina; Ryan, Dylan Gerard; Young, Timothy; et al. (Nature Communications, 2022)
Metabolic reprogramming is critical for tumor initiation and progression. However, the exact impact of specific metabolic changes on cancer progression is poorly understood. Here, we integrate multimodal analyses of primary and metastatic clonally-related clear cell renal cancer cells (ccRCC) grown in physiological media to identify key stage-specific metabolic vulnerabilities. We show that a VHL loss-dependent reprogramming of branched-chain amino acid catabolism sustains the de novo biosynthesis of aspartate and arginine enabling tumor cells with the flexibility of partitioning the nitrogen of the amino acids depending on their needs. Importantly, we identify the epigenetic reactivation of argininosuccinate synthase (ASS1), a urea cycle enzyme suppressed in primary ccRCC, as a crucial event for metastatic renal cancer cells to acquire the capability to generate arginine, invade in vitro and metastasize in vivo. Overall, our study uncovers a mechanism of metabolic flexibility occurring during ccRCC progression, paving the way for the development of novel stage-specific therapies.